“El científico camuflado”, de Peter J. Bentley - Ortega San Martín, Luis (2013)
Short review of the most important and interesting passages of the popular science book “El científico camuflado”, by Peter J. Bentley. Ariel: Barcelona, 2009. 314 pages. ISBN: 978-84-344-8823-6